Sistem Informasi Administrasi dan Computerized Maintenance Management System pada Perusahaan Persewaan Truk X - Vincentius Tandy Prasetyo; Alexander Setiawan; Yulia Yulia (Jurnal Infra, 2020)
PT X is a truck rental service company in Surabaya. The purpose of making a website based administrative information system so that the owner can check and make real-time rental booking transactions, and can generate reports on orders, purchases, inventory, truck repair history are needed for the owner PT. X in making business decisions.Based on the results of this thesis research, it can be concluded that overall this program has fulfilled the needs of PT. X mainly on the function of calculating the cost of orders, updating the price of spare parts on the stock card when purchasing parts, calculating the cost of repairing trucks based on the total price of spare parts used, notifications of repair of periodic oil changes based on kilometers exceeding the next period kilometers.